Patient experiences with self-monitoring renal function after renal transplantation: results from a single-center prospective pilot study - van Lint CL; van der Boog PJM; Wang W; Brinkman WP; Rövekamp TJM; Neerincx MA; Rabelink TJ; van Dijk S (Patient Preference and Adherence, 2015)
Céline L van Lint,1 Paul JM van der Boog,1 Wenxin Wang,2,3 Willem-Paul Brinkman,2 Ton JM Rövekamp,3 Mark A Neerincx,2 Ton J Rabelink,1 Sandra van Dijk1,4 1Department of Nephrology, Leiden University Medical Centre (LUMC), Leiden, 2Faculty of Electrical Engineering, Mathematics and Computer Science, Delft University of Technology, Delft, 3Department of Technology in Healthcare, Prevention and Health, Dutch Organization for Applied Scientific Research (TNO), Leiden, 4Department of Health, Medical and Neuropsychology, Faculty of Social and Behavioural Sciences, Leiden University, Leiden, the Netherlands Background: After a kidney transplantation, patients have to visit the hospital often to monitor for early signs of graft rejection. Self-monitoring of creatinine in addition to blood pressure at home could alleviate the burden of frequent outpatient visits, but only if patients are willing to self-monitor and if they adhere to the self-monitoring measurement regimen. A prospective pilot study was conducted to assess patients’ experiences and satisfaction.Materials and methods: For 3 months after transplantation, 30 patients registered self-measured creatinine and blood pressure values in an online record to which their physician had access to. Patients completed a questionnaire at baseline and follow-up to assess satisfaction, attitude, self-efficacy regarding self-monitoring, worries, and physician support. Adherence was studied by comparing the number of registered with the number of requested measurements.Results: Patients were highly motivated to self-monitor kidney function, and reported high levels of general satisfaction. Level of satisfaction was positively related to perceived support from physicians (P<0.01), level of self-efficacy (P<0.01), and amount of trust in the accuracy of the creatinine meter (P<0.01). The use of both the creatinine and blood pressure meter was considered pleasant and useful, despite the level of trust in the accuracy of the creatinine device being relatively low. Trust in the accuracy of the creatinine device appeared to be related to level of variation in subsequent measurement results, with more variation being related to lower levels of trust. Protocol adherence was generally very high, although the range of adherence levels was large and increased over time.Conclusion: Patients’ high levels of satisfaction suggest that at-home monitoring of creatinine and blood pressure after transplantation offers a promising strategy. Important prerequisites for safe implementation in transplant care seem to be support from physicians and patients’ confidence in both their own self-monitoring skills and the accuracy of the devices used. Keywords: adherence, blood pressure, creatinine, kidney transplantation, satisfaction, self-monitoring